Synthesis of CdS Sensitized TiO2 Photocatalysts: Methylene Blue Adsorption and Enhanced Photocatalytic Activities - A. B. Makama; A. Salmiaton; E. B. Saion; T. S. Y. Choong; N. Abdullah (International Journal of Photoenergy)
A series of CdS/TiO2 nanocomposites with different Cd to Ti molar ratio were synthesized from P25-TiO2 nanopowder using microwave-assisted hydrothermal method. The as-produced powders were characterized by XRD, electron microscopy, EDX, and UV-Vis diffuse reflectance spectroscopy. The adsorption capacity and photocatalytic activity of the samples were investigated using methylene blue as a model pollutant. Sorption tests revealed that the adsorption of MB onto the samples obeys the Freundlich-Langmuir isotherm model. The sorption capacity decreased as follows: TiO2>TCd2>TCd1>TCd3>TCd4. The results of the photocatalytic tests under high-intensity discharge (HID) lamp revealed that CdS/TiO2 powders with low Cd to Ti molar ratios exhibited much higher activities than P25-TiO2. The CdS/TiO2 sample with 20% CdS/(TCd2) showed the most activity among all these samples. The results also show that the Cd to Ti molar ratio of the nanocomposite has a significant effect on the photodegradation of MB and the enhanced activities exhibited by the nanocomposites are because of the low rate of electron-hole recombination.